Hand function improving in patients with cerebral palsy - Lewandowska, Anna; Ratuszek-Sadowska, Dorota; Kuczma, Monika; Kuczma, Waldemar; Hoffman, Jarosław; Hagner, Wojciech (Journal of Education, Health and Sport, 2018)
The hand is an organ of our body that fulfills a lot of different functions. Through efficiently functioning upper limbs, we experience and learn, communicate with the world, and gain independence. In the cerebral palsy, the role of the therapist is to properly plan the hand therapy process, it requires him to have a good knowledge of what MPD is, which is associated with movement symptoms and coexisting disorders that affect the child’s abnormal development. The physiotherapist must properly assess the child’s functional level, anticipate and plan therapy so that the child reaches its maximum development potential. This is not an easy task because virtually every child with cerebral palsy is different, other are its movement limitations, accompanying symptoms and the environment in which he is brought up.